Selection of habitat and resources during migration by a large mammal : a case study of moose in northern Sweden - Lindberg, Jens (SLU/Dept. of Wildlife, Fish and Environmental Studies, 2013)
Migration is a worldwide phenomenon that has occurred for thousands of years in a vast variety of species. The general knowledge of migrating animals is poor even though billions of animals from a range of different groups migrate every year. The human impact on migrating ungulates is high and many populations are declining globally due to direct and indirect causes. Hence it becomes vital to study the migration phase and the habitat and resources selected during migration. The objective with this study was to identify the habitat characteristics and resource selection of moose during migration and compare the selection between different seasons and utilization distribution (relative frequency distribution for the points of location of an animal over a period of time) categories. The study area is located in northern Sweden stretching from 64-67O N in the inland and mountain regions of Västerbotten county. I used GPS tracking data from 49 individual moose represented by 87 moose-years between 2004 and 2010. BBMM (Brownian bridge movement model) and buffer zones were used to describe used and available habitat. BBMM was used since it takes the time interval and trajectory between the locations into account unlike many other models for estimating utilization distribution. The results show that there are differences both between different seasons and different utilization categories. Some individuals select different migration paths depending on season but also that many migration routes were being used both seasons. Moose seems to use migration paths that results in a low cost of energy and where there is a good amount of high quality food. Sometimes it’s unclear when a moose begins or end its migration and therefore problematic to delimit the whole migration path. The definition used in this study can possibly be improved by defining the home ranges in a different way. It would be interesting to analyse the ratio between the different habitat variables in order to see how they affect each other.